Методологічні засади маркетингового забезпечення комерціалізації інтелектуальної власності - Перерва, Петро Григорович; Маслак, Марія Володимирівна; Кобєлєва, Анна Валеріївна (Одеський національний політехнічний університет, 2022)
Розглянуто теоретико-методологічні питання маркетингового забезпечення інтелектуальних технологій. Проведено дослідження сутності терміну «інтелектуальна власність» та на основі узагальнення існуючих пропозицій різних дослідників надано авторське визначення цієї дефініції. Категорію «інтелектуальна власність» запропоновано розуміти як систему відносин, що виникають у процесі створення та використання інтелектуального продукту, а також розподілу результатів цього використання. У цьому визначенні поєднані ключові складові системи відносин власності: права володіння, користування та розпорядження об'єктами власності, а також головна характеристика об'єктів – їхня приналежність до інтелектуального продукту. Основною складовою маркетингового забезпечення інтелектуально-інноваційних технологій визначено ступінь та ефективність їх комерціалізації.

Theoretical and methodological issues of marketing support of intellectual technologies are considered. A study of the essence of the term "intellectual property" and based on the generalization of existing proposals of various researchers provided an author's definition of this definition. The category of "intellectual property" is proposed to be understood as a system of relationships that arise in the process of creating and using an intellectual product, as well as the distribution of the results of this use. This definition combines the key components of the system of property relations: the right of ownership, use and disposal of property, as well as the main characteristic of objects - their belonging to an intellectual product. The degree and efficiency of their commercialization is determined as the main component of marketing support of intellectual and innovative technologies. The main prerequisites for the emergence of the term "intellectual property", which include historical, technological, economic, legal and psychological. The need to separate the need to separate the concepts of "intellectual property", "intellectual capital", "intellectual product" and "intangible assets", which are often used in the same context, but have significant semantic differences. The study of the most commonly used models of commercialization of technologies allows us to identify the following: use in their own production; sale of property rights; licensing; strategic alliance; joint venture; creation of a dedicated enterprise. The level of commercial risk when using different models of technology commercialization is determined. It has been proven that the sale of property rights is the least risky, because in most cases it is a one-time exchange of money for technology.
Methodological principles of marketing support of intellectual property commercialization
Keywords: інтелектуальна власність; комерціалізація; маркетинг; інноваційні технології; ризик; промислові підприємства; intellectual property; commercialization; marketing; innovative technologies; risk; industrial enterprises